Simulation and validation of adsorption process for acrylic acid removal from waste water - Nursakinah, Mat Saad (2013)
The objectives of this study were to develop the mathematical model of the adsorption process of the acrylic acid removal and also to validate the simulation of the adsorption process by using the previous experimental data. The adsorption process is used in the waste water treatment to remove toxic or organic pollutants. Simulation of the adsorption process is necessary to understand the acrylic acid removal using adsorption process. Acrylic acid is removed from the waste water because it can cause serious damage to the environment due to its high toxicity for the aquatic organisms. As a conclusion, the objective is achieved. The new mathematical model of the adsorption process of the acrylic acid by using the activated carbon can created based on the mass balance on the continuous fixed bed column. The validation of the simulation is carried out to compare the simulation data with the experiment data. This research is to improve the understanding of adsorption process of acrylic acid removal from waste water by created the mathematical modeling.